Peran Ambidextrous Leadership Memediasi Hubungan Antara Orientasi Kewirausahaan, Budaya Inovasi Dan Kinerja Sekolah Di Kota Payakumbuh - Andrini, Delvia; Susanto, Perengki (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to determine the role of Ambidextrous Leadership, entrepreneurial orientation and culture of innovation on school performance in SMA and MA Negeri in Payakumbuh. This study is a qualitative research with questionnaires distributed to eight public schools in Payakumbuh. The sampling technique used in this research isSimple random sampling. Data analysis using SEM PLS analysis. The results of the analysis concluded that, Ambidextrous leadership significant effect on school performance. However, Ambidextrous leadership has a significant effect on entrepreneurial orientation. Then the results of this study indicate that entrepreneurial orientation has a significant effect on school performance. Ambidextrous leadership and innovation culture have no significant effect on school performance or innovation culture does not moderate the relationship between ambidextrous leadership and school performance. Entrepreneurial orientation and innovation culture have no significant effect on school performance or innovation culture does not moderate the relationship between entrepreneurial orientation and school performance.